Role of peptide–cell surface interactions in cosmetic peptide application - He, Bingwei; Wang, Feifei; Qu, Liping (Frontiers in Pharmacology, 2023)
：Cosmetic peptides have gained popularity in a wide range of skincare products due to their good biocompatibility, effective anti-oxidative, and anti-aging effects. However, low binding between peptides and the cell surface limits the efficacy of functional peptides. In this study, we designed two novel targeting peptide motifs to enhance the interaction between cosmetic peptides and the cell surface, thereby improving their performances for skin health. To achieve this, we optimized the well-known peptide Tripeptide-1 (GHK) by separately grafting the integrin αvβ3-binding motif RGD and the chondroitin sulfate (CS)-binding motif sOtx2 onto it, forming two chimeric targeting peptides, RGD-GHK and sOtx2-GHK. Comparative analysis showed that both RGD-GHK and sOtx2-GHK exhibited superior anti-oxidative and antiapoptotic effects compared to the non-targeting peptide, GHK. Furthermore, RGD-GHK demonstrated exceptional anti-aging activity, and its potential for promoting wound healing and repairing the skin barrier was evaluated in vitro using cells and skin models. In vitro permeation and in vivo adsorption test confirmed that RGD-GHK achieved a high local concentration in the skin layer, initiating peptide effects and facilitating in vivo wound healing, while maintaining excellent biocompatibility. The enhancement of signaling cosmetic peptides can be attributed to the specific interaction between the binding motif and cell surface components. Consequently, this targeting peptide holds promising potential as a novel functional peptide for application in cosmetics.